Uganda - Adjustment Operations in Support of Education - Murphy, Patrick D. (2012)
In a bold effort to achieve Universal Primary Education (UPE) by 2000, the Government of Uganda decided in 1996 to remove primary school fees for up to four children in each family (of whom two should be girls). The World Bank supported this effort through an Education Sector Adjustment Credit and Grant (ESAC). The ESAC was designed to assist the government deal with the immediate challenges arising from the UPE policy. The broad development objective of ESAC was to ensure that the public resources needed to sustain UPE were available and that there was improved allocation and more efficient use of these resources. In addition and critically for the Bank the operation was designed to enhance the availability of quality inputs and improve overall sector management.